Public international law with regard to the social consequences of the development of genetics - Kwiatkowski, Paweł (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2016)
The extension of international instruments in the field of human rights to embrace a bioethical perspective constitutes a response from international organisations to the social consequences of the development of genetics. These initiatives led in turn to the formation of universal norms of a declarative nature, as well as legally binding norms for the states of the Council of Europe. The author focuses on the basic principles of: the Universal Declaration on the Human Genome and Human Rights, the International Declaration on Human Genetic Data, the Universal Declaration on Bioethics and the Human Rights United Nations Declaration on Human Cloning, and the Convention on Human Rights and Biomedicine – presenting the foundations of international bioethics law with regard to the social consequences of the development of genetics.